1,5-Acrylodan: A Fluorescent Bioconjugate Sensor of Protic Environments - Jake Morrin; Matthew Petitt; Christopher Abelt (Organics)
1,5-Acrylodan (1-(5-(dimethylamino)naphthalen-1-yl)prop-2-en-1-one) is prepared in six steps from 1-nitronaphthalene and 19% overall yield. The last three steps involve an aryllithium-directed nucleophilic addition, catalytic Kulinkovich cyclopropanation, and copper-catalyzed oxidative ring-opening to generate the acryloyl moiety. The fluorescent properties of 1,5-Acrylodan (AC) are reported. These include its solvatochromism and H-bond quenching by protic solvents. Its use as a bioconjugate sensor is demonstrated with Human Serum Albumin (HSA) through its covalent attachment to Human Serum Albumin (HSA) at the free cysteine-34 moiety. Unfolding studies with guanidinium chloride (GdmCl) and sodium dodecyl sulfate (SDS) are conducted to illustrate how the fluorophore responds to changes in both micropolarity and exposure to water.